Radiocarbonscapes of Sedimentary Organic Carbon in the East Asian Seas - Bao, Rui; Blattmann, Thomas M. (Frontiers in Marine Science, 2020)
Natural abundance radiocarbon (14C) is an increasingly widely used tool for investigating the organic carbon (OC) cycle in the contemporary ocean. Recent studies have provided extensive information on the 14C characteristics of organic matter (OM) in sinking particles and sediments in the East Asian Seas including studies from the Bohai Sea, Yellow Sea, East China Sea, South China Sea, Japan Sea, and Japan Trench. 14C investigations have provided insights into biogeochemical processes controlling the fate of sedimentary OM in these settings. Here, we highlight these insights from oceanic landscapes stretching across deltas, shelves, abyssal oceans, and the hadal zones of the East Asian Seas, share our perspectives on the source-to-sink dynamics of sedimentary OM in the ocean, and outline the challenges that need to be faced to make the most out of interpreting 14C signals in sedimentary OC.